Achievement of essentially full spatial coherence in a high-average-power soft-x-ray laser - Attwood, D. T., author; Rocca, Jorge J., author; Chang, C., author; Tomasel, F. G., author; Seminario, M., author; Liu, Y., author; American Physical Society, publisher (Colorado State University. Libraries, 2001)
We report an observation of essentially full spatial coherence in a high average power soft-x-ray laser. Rapid coherence buildup due to strong refractive antiguiding in a long plasma column is experimentally demonstrated. This allows the generation of fully coherent, milliwatt-level average power soft-x-ray radiation by a tabletop device. The peak brightness of this laser reaches 2×1025 photons s-1 mm-2 mrad-2 within 0.01% spectral bandwidth, making it one of the brightest soft-x-ray sources available.